Hubungan Motivasi Belajar Dan Pañcasila Buddhis Terhadap Kematangan Karir Pada Siswa SMA Negeri 1 Donorojo di Kabupaten Jepara - Retnoningsih; Kabri Kabri; Utomo, Budi (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Specific research on factors influencing career maturity, including learning motivation and Buddhist Pancasila at Donorojo 1 Public High School, Jepara Regency, is still lacking. This study uses a quantitative method with a causal associative research design. The research population consists of 52 students, and the sample used is the entire student body. The data collection method is a questionnaire. The instrument used in this study is a questionnaire sheet. The data analysis technique uses inferential statistical analysis. The results of data analysis show that there is a significant positive effect between learning motivation and career maturity of 69.4%. In addition, there is a significant positive relationship between Buddhist Pañcasila and student career maturity of 64.9%. Furthermore, there is a significant positive relationship between learning motivation and Buddhist Pañcasila and student career maturity of 82.5%. It can be concluded that the higher a person's learning motivation, the stronger the student's career maturity. In addition, the better the quality of the student's Buddhist Pañcasila, the higher the student's career maturity. Thus, the higher the learning motivation and the better the Buddhist Pañcasila, the stronger the student's career maturity will be.